Character Development in Reading Folktales: Literacy Learning Strategies Using Propp’s Dramatis Personae and Narrative Functions in Princess Hase - Rachmawati, Amalia; Tjahjono, Tengsoe; Raharjo, Resdianto Permata; Purwati, Oikurema (IJET (Indonesian Journal of English Teaching), 2023)
This study intended to explore one of the literacy learning strategies namely character development in reading that can be used in the classroom by combining with Propp’s dramatis personae framework to get the deeper understanding about the folktales. This study involved the Japanese Folktale entitled Princess Hase as this story contains moral value that can be obtained by students after reading the folktales. This study used qualitative descriptive method which emphasizes on dramatis personae that exist in the folktales to get the deeper understanding. This study found out that the application of Propp’s dramatis personae in analyzing folktales can make the readers easier in understanding the folktales. Moreover, the combination of literacy learning strategies in this case character development in reading with Propp’s dramatis personae is beneficial to be applied in the classroom.